Osmotic and "toxic" effects of salinity on germination of Phaseolus vulgaris L. seeds - Prisco, José Tarquinio; O'leary, James W. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Do not present work, feijão seeds "red kidney" (Phaseolus vulgaris L.) foram seeded in substrates containing solutions of NaCl and Cambowax 1540. The water powers of the substrates foram: 0, -2, -4, -8, -12, e-16 bars. The absorption of water by seeds can be considered in two stages. At first they depend mainly on the matrix potential of the seeds, while in the second they function from the osmotic pressure of themselves. For non-substrate water potential values ​​of -8 to 16 bars Carbowax inhibited more water absorption and root emersion than NaCl. When seeds are subjected to water potentials in the range of 0 to 8 bars, the NaCl effect in germination was mainly osmotic. However, in low damage potential (-12 bars) the inhibition of germination was due to osmotic and toxic effects. The difference in values ​​found between root engulfment and germination suggests that at first it is not a good criterion for germination. The effects of salinity in the germination and subsequent development of seedlings are toxic and osmotic foram Carbowax 1540. They do not seem to have a toxic effect, as in the germination, rather than in the development of seedlings.